2002
DOI: 10.2320/matertrans.43.1868
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Properties of Liquid Al-Sn-Zn Alloys: A Possible New Lead-Free Solder Material

Abstract: Because of its potential to be used as a lead free solder material the thermodynamic properties of the liquid Al-Sn-Zn system were investigated. Using an appropriate galvanic cell, the partial free energies of Al were determined as a function of concentration and temperature. Thermodynamic properties were obtained for 30 alloys. Their composition was situated on three cross-sections with constant ratios of Sn:Zn = 2:1, 1:1 and 1:2. The integral Gibbs energy and the integral enthalpy for the ternary system at 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 36 publications
0
36
0
Order By: Relevance
“…18) Earlier, a thermodynamic assessment of the ternary system was reported by Fries et al 19) However, in view of recent experimental thermodynamic data of the liquid phase 20) 21) and also previous CALPHAD calculation. 19) However, these results offers no significant advantage over binary Sn-Zn eutectic.…”
Section: Al-sn-zn Systemmentioning
confidence: 99%
“…18) Earlier, a thermodynamic assessment of the ternary system was reported by Fries et al 19) However, in view of recent experimental thermodynamic data of the liquid phase 20) 21) and also previous CALPHAD calculation. 19) However, these results offers no significant advantage over binary Sn-Zn eutectic.…”
Section: Al-sn-zn Systemmentioning
confidence: 99%
“…Al-Sn, Al-Zn and Sn-Zn, has been selected for theoretical investigation. The two other principal reasons considered alongside the ones above are: (i) there seems to be a general consensus among researchers that the composition of new lead-free solders would be based on low-melting metals, and Sn and Zn seem to be the most promising ones, and (ii) the potential of Al-Sn-Zn for developing an alternative for lead-free solder [6,10] and/or its viability as a subsystem for developing complex alloy systems, such as the Al-Sn-Zn-Ag, have been reported in the literature [10,15].…”
Section: Introductionmentioning
confidence: 99%
“…Majority of investigated alloy systems are Sn-based, having Al, In, Sb, Zn, Bi, Au, Tl and Ag as a part of the alloy constituents. In particular, the studies have indicated Sn to be the major component in binary solders and that Sn-based multi-component alloys, such as ternary (Al-Sn-Zn, In-Sn-Zn, Sn-Ag-Cu) and/or quaternary (Sn-Ag-Cu-Sb, Sn-Ag-Cu-Zn) systems are more favored as a primary high-temperature alternative for lead-free solder [1,6,8]. Accordingly, the ternary Al-Sn-Zn alloy which is considered as an important system in lead-free soldering together with its binary subsystems, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations